2013
DOI: 10.1103/physrevc.87.054909
|View full text |Cite
|
Sign up to set email alerts
|

Spectator-induced electromagnetic effect on directed flow in heavy ion collisions

Abstract: We estimate the electromagnetic effect of the spectator charge on azimuthal anisotropies observed in heavy ion collisions. For peripheral Pb+Pb reactions at the top energy of the CERN Super Proton Synchrotron, √ s N N = 17.3 GeV, we predict this effect to bring very large distortions to the observed directed flow, v 1 , of positive and negative pions emitted close to beam rapidity. The overall magnitude of this effect is comparable to values of v 1 reported by the WA98 experiment. We argue that also at lower r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 57 publications
4
42
0
Order By: Relevance
“…Our analysis of charged pion directed flow in Pb+Pb collisions [4] demonstrated that the spectator-induced electromagnetic effect results in very large absolute values of v 1 for positive pions at target and beam rapidities, in agreement with data from the WA98 experiment [5]. This suggests the emission site of these pions to be placed relatively close to the corresponding spectator system, at a longitudinal distance d E below 1 fm.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our analysis of charged pion directed flow in Pb+Pb collisions [4] demonstrated that the spectator-induced electromagnetic effect results in very large absolute values of v 1 for positive pions at target and beam rapidities, in agreement with data from the WA98 experiment [5]. This suggests the emission site of these pions to be placed relatively close to the corresponding spectator system, at a longitudinal distance d E below 1 fm.…”
Section: Introductionsupporting
confidence: 72%
“…Putting the result of this simplified study (d E ≈ 3 fm) in the context of our earlier analysis of pion directed flow at target and beam rapidities (where a value of d E below 1 fm could be deduced from the data [4]), we note that the obtained effective value of d E decreases with increasing c.m.s. rapidity of the pion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-central collisions unambiguously lead to azimuthal asymmetries in the pion trajectory [1], which may be linked to the electromagnetic field generated by these fast-moving charged remnants. The influence of this field on charged pions was discussed in [2,3].…”
Section: Introductionmentioning
confidence: 99%